Formulation Of Nao Equation According To Nao Framework - Abdul Rasib, Amir Hamzah; Musazali, Mussyahirah (Science Research Society, 2021)
Companies in manufacturing often find strategies to increase production efficiency and quality to be competitive in the long run. These strategies make companies remain profitable in a highly competitive market. Nonetheless, attempting to maintain a shorter production lead time is also vital as efficiency becomes a competitive priority. Whenever there are longer lead times, overtime is taken into account to meet the target. Overtime can be the most cost-effective way for companies to achieve their quality needs. Nevertheless, if poorly managed, overtime could quickly outstrip financial gains. This study aimed to establish the manufacturing industry model of non-value-added overtime (NAO) and formulate NAO equations. In this regard, the NAO equations were acquired from the critical factors of NAO. The vital aspects of NAO were then presented through the activities flow in the input/output manufacturing concept. The study results indicated that the highest critical factors contributed to the three processes: pre-process, in-process, and post-process.